Sufism in the lyrics of the song "Mardatilla" by Rhoma Irama: An analysis of Sufistic metaphors - Hidayat, Yogi Fery (Jurnal Penelitian Humaniora, 2025)
Sufism plays a very important role in today's era. Amid the busyness and complexities of modern life, many people feel lost and confused in their search for meaning and purpose in life. This study aims to analyze the Sufi metaphors found in the lyrics of the song "Mardatilla" by Rhoma Irama, which conveys messages about Sufism. The analysis method used in this research is Sufi metaphor analysis, which refers to Sufi theories and the understanding of metaphor as a means to gain deeper insight into spiritual concepts or truths. The data analyzed consists of the lyrics of "Mardatilla," selected based on the richness of Sufi metaphors contained within. The results of the study show that the lyrics of "Mardatilla" contain many Sufi metaphors representing spiritual concepts and experiences in Sufism, such as worship, spiritual experiences, love and loyalty to God, and transcendental experiences. Thus, this study can contribute to the understanding of Sufism through the analysis of Sufi metaphors found in popular art forms such as music.